Upaya Peningkatan Penghasilan Tambahan Kelompok Budidaya Lele Di Kecamatan Mojo Kabupaten Kediri - Nurlailiyah; Rima ariani; Lela Puspitasari; Atika Amiril Amaliya; Bintis Tianatud Diniati (Fakultas Tarbiyah IAIN Kediri, 2024)
This research aims to increase additional income through empowering catfish cultivation groups in Mojo District, Kediri Regency. Mojo District has great potential with green land, fertile soil and abundant water availability. The catfish farming group in Ngadi Village, which consists of six members, has been established since 2010. Even though the group members have permanent jobs as farmers and traders, the income they earn is not sufficient for their needs. Community empowerment through catfish cultivation is expected to increase the income of group members. Catfish was chosen because it has high economic value and large market demand. Apart from that, cultivating catfish can improve people's skills, knowledge and health. The method used in this research is qualitative with observation techniques, in-depth interviews and documentation. The research was conducted in Mojo District, Kediri Regency, in October 2024. The results of the research show that catfish cultivation can increase the income of group members, make a positive contribution to the welfare and independence of the community, as well as make optimal and sustainable use of natural resources. The importance of the results of this research is that it provides useful recommendations for the development of catfish cultivation businesses and community empowerment in Mojo District, as well as showing how utilizing empty land can be a solution to meet economic needs.